SWOT Analysis of the Planning Strategy of the Lake Teluk Gelam Tourism Area, Ogan Komering Ilir Regency - Ahmad Fuad; Abdiyanto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Tourism is considered one of the fastest-growing industries in the world, as it is one of the most important sectors of the economy that contributes to providing currency and boosting local development by creating job opportunities through investors. Indonesia has become a popular tourist destination with a variety of beautiful natural tourism making Indonesia the largest archipelagic country and one of the most attractive tourist destinations. Strategic planning of tourist areas aims to develop tourist areas in a sustainable manner. One of them, the Teluk Gelam Lake area, Teluk Gelam Lake was designated by the South Sumatra Provincial Government as a provincial tourism object. The potential of the Teluk Gelam Lake Area refers to the concept of Ecotourism. Based on this potential, a special strategy is needed in planning Lake Teluk Gelam tourism, so that tourism potential can be developed optimally so that there are no losses to the development of the region itself. This study uses literature study and SWOT analysis. The results of Swot show that the Power of Agrotourism has the potential to increase public awareness of sustainable development Agrotourism activities can be a tool for the preservation of cultural identity, to further develop local communities and to offer a fair allocation of resources. Disadvantages Being in a watershed (watershed) has several problems that need to be taken seriously. First, the local community lacks knowledge about environmental conservation, the Teluk Gelam Lake Area Opportunity has very good tourism opportunities in planning the determination of the tourism sector. One form of tourism that can be developed in this area is ecotourism from the natural tourism of Lake Teluk Gelam. Threat The threat to the Lake Gelam Tourism area is ecological damage due to massive human activities. Watersheds (Watersheds) that are the scope are very vulnerable to environmental changes.